Comparative Urban Studies and African Studies at the Crossroads: From the Colonial Situation to Twilight Institutions - (:unkn) unknown (My University, 2023)
Calls for the development of urban theory based on comparative research on African cities have become increasingly common. In the last 20 years, an emerging body of work in history, anthropology, and political science has re-evaluated the role of state and non-state institutions in shaping forms of urbanism and urbanization in innovative ways. In Sociologie des Brazzavilles noires, published in 1955, Georges Balandier explored the distinctive features of Bacongo and Poto-Poto, two fast growing campements de travailleurs of the headquarters of French Equatorial Africa. The concept ‘twilight institutions’ politicized non-statutory or informal institutions providing services and public goods. The notion of ‘twilight institutions’ fits well with contemporary harsh urban and rural life conditions in the continent, damaged by two decades of IMF policies, and challenges the idea of urbanization as a problem which remains dominant in many development and urban studies narratives.
Keywords: African Research